Come hell or highball [large type] : a mystery - Chance, Maia (Chance, Maia. Discreet Retrieval Agency mystery., 2016)
Society matron Lola Woodby survives her loveless marriage until her husband dies suddenly and leaves her a big pile of debt. Soon Lola and her stalwart Swedish cook, Berta, are reduced to accepting an offer from one of his girls-on-the-side: for a handsome sum, Lola is to retrieve a mysterious reel of film.